Improvements of simulated Western North Atlantic current system and impacts on the AMOC - Talandier, Claude; Deshayes, Julie; Treguier, Anne-marie; Capet, Xavier; Benshila, Rachid; Debreu, Laurent; Dussin, Raphael; Molines, J. -m.; Madec, Gerard (Ocean Modelling, 2014)
Previous studies have shown that low horizontal resolution (of the order of 1°) ocean models, hence climate models, are not able to adequately represent boundary currents nor mesoscale processes which affect the dynamics and thermohaline circulation of the ocean. While the effect of mesoscale eddies can be parameterized in low resolution models, boundary currents require relatively high horizontal resolution. We clarify the impact of increasing the resolution on the North Atlantic circulation, with emphasis on the Atlantic Meridional Overturning Circulation (AMOC), by embedding a 1/8° nest covering the North Atlantic into a global 1/2° model. Increasing the resolution in the nest leads to regional improvements of the circulation and thermohaline properties in the Gulf Stream area, for the North Atlantic Current, in the subpolar gyre and the Nordic Seas, consistent with those of previous studies. In addition, we show that the Deep Western Boundary Current dense water transport increases with the nest, from the overflows down to Flemish Cap, due to an increase in the Denmark Strait overflow as well as dense water formation in the subpolar gyre. This increases the Atlantic Meridional Overturning Circulation in density space by about 8 Sv in the Subpolar gyre in the nested configuration. When exiting the Labrador Sea around 53°N we illustrate that the Deep Western Boundary Current successively interacts with the upper ocean circulation composed with the North Atlantic Current in the intergyre region, the Northern Recirculation Gyre, and the Gulf Stream near Cape Hatteras. This surface/deep current interaction seems to induce an increase of the AMOC intensity in depth-space, giving rise to an AMOC maximum near 35°N. This process is missing in the configuration without nesting. At 26.5°N, the AMOC is 4 Sv larger in the nested configuration and is in good agreement with observations. Finally, beyond the nest imprint (i.e. in the low resolution area) in the South Atlantic the AMOC maximum at 40°S is 3 Sv larger at the ...